Pengaruh Good Governance dan Budaya Organisasi Terhadap Kinerja Manajerial Penyelenggara Pemerintahan Desa di Kabupaten Badung - Widasari, Kadek Indah; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Akuntansi, 2018)
Undang-Undang No. 6 of 2014 about the village is the embodiment of Nawa Cita third priority which states build Indonesia starting from the edge by strengthening the regions and villages within the framework of the unitary state. The reality is still found many weaknesses of the village government officials in carrying out the mandate of Undang-Undang No.6 of 2014. This research aims to examine the influence of Good Governance and organizational culture to the managerial performance of village government officials in Badung regency. Badung regency has a total of 46 village, sample determination using probability sampling with Slovin technique. Respondents of this research are Village Head, Village Secretary, Finance Chief, Village Consultative Board (BPD) and Community Empowerment Institution (LPM) in each village in Badung Regency with 80 respondents. Data analysis technique in this research use Multiple Linear Regression Analysis. The results of this research indicate that the variables of Good Governance, organizational culture, and competence have a positive effect on the managerial performance of village government officials in Badung Regency. Keywords : Good governance, Organizational Culture, Managerial Performance